Dialysis Treatments and Nursing Care in Disasters - Aksoy, Tülay; Pehlivan, Gülseren (Cerrahpaşa Medical Journal, 2023)
Disasters are situations that cause harm and loss of life and property that go beyond what a society can handle using its own resources to function. Earthquake victims are at risk of developing crush syndrome, so it is crucial that earthquake victims who are buried under the debris in collapsed buildings are taken to hospitals as quickly as possible after being freed from the debris. If the crush syndrome is not treated quickly and efficiently, it might result in acute kidney injury (AKI). Children, however, are at a lesser risk due to their smaller body surface area than adults. Dialysis is lifesaving when AKI is irreversible despite medical intervention. A holistic nursing approach is used to assess acute or chronic patients getting dialysis therapy, identify their care requirements, and deliver the necessary care. Patients receiving hemodialysis and peritoneal dialysis should be informed about what to do in case of an earthquake and should take the appropriate safety measures in case of emergencies in dialysis facilities in order to recover with the least amount of damage. Cite this article as: Aksoy T, Pehlivan G. Dialysis treatments and nursing care in disasters. Cerrahpaşa Med J. 2023;47(S1):42-46.